Dependencia emocional según la teoría de Jorge Castelló: un estudio de caso - Alalú de los Ríos, Deborah (2016)
The aim of this research was to exemplify, by the study, development and analysis of a clinical case, the theory proposed by Jorge Castelló Blasco (2005) about the construct of emotional dependence. The type of research was a single type case. Therefore, a 36- year-old woman, who was diagnosed with major depression by a health professional, was evaluated. The techniques for collecting information and instruments used were: Subject´s behavior observation, interview and anamnesis, BarOn Quotient Emotional Inventory, Revised Neo Pi-R Inventory, Millon Clinical Multiaxial Inventory II, Emotional Dependency Inventory – IDE, Emotional Dependence Clinical Interview and an interview to a close person. The results obtained allows us to exemplify Castello´s theory (2005) and its aspects about the emotional dependency. In adittion, the diagnosis of major depression was replaced by the emotional dependence diagnosis.